The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1016/j.acn.2008.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two scoring systems of the Rey–Osterrieth Complex Figure in left and right temporal lobe epileptic patients

Abstract: The Rey-Osterrieth Complex Figure (ROCF) is probably one of the most popular measurement instruments of visuoconstructional abilities and nonverbal memory. It is frequently part of neuropsychological test protocols in epilepsy surgery centers. In this study we compared the traditional scoring system of the ROCF developed by Taylor (1998) with a qualitative system that assesses spatial-relational errors devised by Loring et al. [Loring, D. W., Lee, G. P., & Meador, K. J. (1988). Revising the Rey-Osterrieth: Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Generally, the copy condition ought to assess visuoconstructional, visuospatial, planning/organizational and graphomotor skills, while the recall condition additionally assesses visual memory capacities (Ruffolo, Javorsky, Tremont, Westervelt, & Stern, 2001). To the best of our knowledge, so far only one study has compared different scoring systems of the ROCFT in a clinical sample: Frank and Landeira-Fernandez (2008) found performance differences on the ROCFT between patients with left versus right temporal lobe epilepsy upon using a qualitative scoring system, while quantitative scoring approaches failed to detect significant group differences.…”
Section: Scoring Systems Of the Rey-osterrieth Complex Figure Test (Rmentioning
confidence: 91%
“…Generally, the copy condition ought to assess visuoconstructional, visuospatial, planning/organizational and graphomotor skills, while the recall condition additionally assesses visual memory capacities (Ruffolo, Javorsky, Tremont, Westervelt, & Stern, 2001). To the best of our knowledge, so far only one study has compared different scoring systems of the ROCFT in a clinical sample: Frank and Landeira-Fernandez (2008) found performance differences on the ROCFT between patients with left versus right temporal lobe epilepsy upon using a qualitative scoring system, while quantitative scoring approaches failed to detect significant group differences.…”
Section: Scoring Systems Of the Rey-osterrieth Complex Figure Test (Rmentioning
confidence: 91%
“…The ROCF has a long history in neuropsychology both in clinical and research settings: it is used to assess a variety of cognitive processes such as visuo‐spatial functions, visual episodic memory, planning, organizational skills, problem‐solving, executive functions, visuo‐motor coordination, and constructional praxis (Meyers & Meyers, ). Accordingly, this test has been administered to patients with traumatic brain injuries (Bigler, ), amnesia (Kixmiller, Verfaellie, Mather, & Cermak, ), dementia (Pelati et al ., ), and epilepsy (Barr et al ., ; Frank & Landeira‐Fernandez, ; Wisniewski, Wendling, Manning, & Steinhoff, ), but it has been used also in psychiatric populations, such as patients with obsessive‐compulsive disorders or schizophrenia (Kim, Namgoong, & Youn, ; Seidman, Lanca, Kremen, Faraone, & Tsuang, ; Shin et al ., ). The ROCF can be administered to both children (Mati‐Zissi & Zafiropoulou, ) and elderly people (Elderkin‐Thompson et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies suggested lower results for Immediate Recall and Delayed Recall tasks on nonverbal material in patients with right-sided TLE. Frank and Landeira-Fernandez off er an explanation for the diffi culty of reproducing this fi nding in our study, indicating that the fi gural stimulus used for testing nonverbal memory is not optimally constructed 21 . Th ey suggest that fi gural stimuli can be verbalized and modifi ed as linguistic stimuli, i.e.…”
Section: Discussionmentioning
confidence: 55%
“…Previous research has clearly demonstrated the comorbidity of depression and anxiety with epilepsy [22][23][24][25][26] . Nine (15%) participants in our study were depressed, while seven (12%) had signifi cantly elevated anxiety.…”
Section: Discussionmentioning
confidence: 99%